2009
DOI: 10.2139/ssrn.1022467
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Search Engine Advertising: Sponsored Search in Electronic Markets

Abstract: T he phenomenon of sponsored search advertising-where advertisers pay a fee to Internet search engines to be displayed alongside organic (nonsponsored) Web search results-is gaining ground as the largest source of revenues for search engines. Using a unique six-month panel data set of several hundred keywords collected from a large nationwide retailer that advertises on Google, we empirically model the relationship between different sponsored search metrics such as click-through rates, conversion rates, cost p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
217
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(239 citation statements)
references
References 40 publications
20
217
0
1
Order By: Relevance
“…Athey and Meidan (2011) and Athey and Nekipelov (2011) are important papers on the analysis of user behavior in the paid results. Previous research has indicated that CTRs can increase markedly for results placed at the top of a results page compared to other ranks and pages (Smith and Brynjolfsson 2001;Xu and Kim 2008;Ghose and Yang 2009. Of these studies, Xu and Kim (2008) is based on a small-sample laboratory experiment, and Xu and Kim (2008) uses data on paid search from an advertiser.…”
Section: Introductionmentioning
confidence: 99%
“…Athey and Meidan (2011) and Athey and Nekipelov (2011) are important papers on the analysis of user behavior in the paid results. Previous research has indicated that CTRs can increase markedly for results placed at the top of a results page compared to other ranks and pages (Smith and Brynjolfsson 2001;Xu and Kim 2008;Ghose and Yang 2009. Of these studies, Xu and Kim (2008) is based on a small-sample laboratory experiment, and Xu and Kim (2008) uses data on paid search from an advertiser.…”
Section: Introductionmentioning
confidence: 99%
“…To be consistent with previous literature (e.g. [9]), we also allow CTR on the search channel to be affected by the position of the ad (Rank).…”
Section: (B) Regression Modelmentioning
confidence: 92%
“…improved rank allocation mechanisms ( [7], [17]); (iii) needs of advertisers -e.g. profitability of ad display rank [9]; (iv) behavior of advertisers, and implications for consumers who click on keyword based ads -e.g. quality uncertainty and adverse selection in performance based search advertising (use of cost per click) [1]; and (v) interaction effects between different aspects of keyword based search, with implications for advertisers -e.g.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In practice, many online sellers rely on keyword advertising to promote their sales in short term with limited budget. Most of the previous researches use direct revenue factors as dependent variables such as CTR (click through rate) and CVI (conversion per impression) in their researches on the keyword advertising [14,16,22,25,31,32]. Previous studies were, however, conducted in the context of aggregate-level due to the limitations on the data availability.…”
mentioning
confidence: 99%